PENGARUH PROFESIONAL, PERTIMBANGAN PASAR KERJA, PERAN GENDER, LINGKUNGAN DAN KELUARGA DALAM PEMILIHAN KARIER AKUNTAN PUBLIK (Studi Empiris pada Mahasiswa Akuntansi di Universitas Islam Malang dan Universitas Negeri Malang) - Siti Wahyuni; Noor Shodiq Askandar; Muhammad Cholid Mawardi (Universitas Islam Malang, 2019)
ABSTRACTThis study aims to examine professional training, labor market considerations, gender, environmental and family roles in the selection of career of a Public Accountant. The object of this research is accounting students Unisma and UM. The sample method is done by random sampling. The number of students sampled in this study was 96 students. The data used are primary data in the form of questionnaires distributed to respondents. The data analysis method used in this study is multiple linear regression analysis. The results of the study show that professional training, labor market, environmental and family considerations have a significant effect on the career choice of a Public Accountant. Gender roles have no significant effect on the career choice of a Public Accountant.Keywords: Professional training, labor market considerations, gender, environmental and family roles, career choice for public accountants